Pengaruh Teknik Relaksasi Distraksi Terhadap Nyeri Pada Pasien Post Operasi Sectio Caesaria di Ruang Inap Kebidanan Rumah Sakit Umum Daerah Embung Fatimah Kota Batam Tahun 2017 - Ditte Ayu Suntara (CV. ADIBA AISHA AMIRA, 2021)
Pain is a sensation sujektif, uncomfortable feeling usually associated with actual or potential tissue damage. Non- pharmacological approaches typically use behavioral therapy (hypnosis, biofeedback), lubricating the muscle / relaxation, acupuncture, cognitive therapy (distraction), cognitive restructuring, imajinasidan physical therapy. lessen the pain suffered by patients and therefore as a matter of research is whether there are benefits perceived by patients with postoperative pain management of pain is done in a relaxing distraction in the general hospital nursing batam city area. Research goal is to find out whether there are differences in the level of pain after the act of distraction in patients post-surgery at Regional General Hospital of the city of Batam. This research includes experimental research design with quasy experiments (pre test - post test control group design). The research sample of 40 patients with 20 patients the intervention group and 20 control group. Results of research conducted in November 2011 until Februari 2012 to 20 control patients without treatment is only given analgesics at 0.5 of pain before the intervention of 6.65 decreased to 6.60 when compared to 20 patients of intervention, previous analgesic decreased 5 7.15, 25 means decreased by 1.9. The effectiveness of a combination of techniques and anelgesik (p = 0.040), Regional General Hospital in the city of Batam. The conclusions of the study, relaxation techniques are needed to relieve pain terrhadap patients. Implications for efforts to carry out research indicated distraction relaxation techniques to relieve pain. Suggestions are advised to hospitals for to make a (soup) operational standards regarding post-surgical pain.